2017
DOI: 10.17776/csj.340483
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oxytocin and Oxytocin Receptor Antagonist Atosiban on the Carbonic Anhydrase and Acetylcholinesterase Enzymes from Lung Tissues of Rats

Abstract: The purpose of our studies is to assist in fully understanding the role of oxytocin in the live metabolism by examining the effects of oxytocin, oxytocin receptor antagonist atosiban, and oxytocinatosiban chemicals injected to the rats on activities of carbonic anhydrase (CA) and acetylcholinesterase (AChE) enzymes in the lung tissue of the rats. For this purpose, 4 different groups each of which contains 6 rats formed. (Control group, oxytocin administered group, atosiban administered group, and both oxytocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The cytosolic forms of carbonic anhydrase enzymes are hCA I and hCA II. hCA I and hCA II isozymes play a role in respiration and acid–base homeostasis, 6–11 pH and bicarbonate homeostasis, many physiological processes including respiration, bone metabolism, and tumor formation. It is involved in the carbon dioxide hydration catalysis of CAs 12–15 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytosolic forms of carbonic anhydrase enzymes are hCA I and hCA II. hCA I and hCA II isozymes play a role in respiration and acid–base homeostasis, 6–11 pH and bicarbonate homeostasis, many physiological processes including respiration, bone metabolism, and tumor formation. It is involved in the carbon dioxide hydration catalysis of CAs 12–15 …”
Section: Resultsmentioning
confidence: 99%
“…CA (carbonate hydrolase, EC 4.2.1.1) is a metalloenzyme that functions in numerous tissues and acts as a catalyst in the reversible hydration of carbon dioxide to bicarbonate. It contains zinc (Zn 2+ ) ions in its active site 6–14 . Carbonic anhydrases are classified into four categories based on where they are found in the body, with at least 16 distinct isoforms ranging from CA I to CA XVI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study demonstrated that OT binding to OT receptors has a protective effect against heat-induced ALI by inhibiting the ischemic, oxidative and inflammatory responses in a rat model. The mechanism might involve TLR4/NLRP3/NF-κB, Bax/p53, Bcl-2 40,41 , type A gamma-aminobutyric acid receptor 28 , calpain-1 7 , and carbonic anhydrase and acetylcholinesterase enzymes 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, for K is , three different concentrations of the compounds ( 3a–j and 5a–f ) were used. [ 41 ] Then, Lineweaver–Burk graphs were drawn according to these measurements. K i values of chalcone derivatives containing Schiff bases ( 3a–j and 5a–f ) were determined from Lineweaver–Burk graphs, as previously described.…”
Section: Methodsmentioning
confidence: 99%